Sakura Hime, the Legend of Princess Sakura. 7 - Tanemura, Arina (Shojo beat manga., 2012)
"Every time Asagiri uses her powers, she shortens her life span. In spite of this, she continues to use her powers to fight her former lover, Ukyo. Though Ukyo will not attack her, this is a fight Asagiri cannot win" -- from publisher's web site.